A Female Multi-Body Head-and-Neck Model and Validation for Rear Impact Simulations - Fatma Nur Şen; Selcuk Himmetoglu (Applied Sciences)
In this study, the development and validation of a 35th percentile female multi-body head–neck model are presented to study whiplash-related disorders in rear-end impacts. The volunteer sled tests conducted by the Japan Automobile Research Institute (JARI) with an impact velocity of 7.9 km/h have been utilized for the validation process. The proposed method in the development of the female multi-body head-neck model is characterized by its simplicity, efficiency, and capability of the biofidelic responses. Compared to the volunteer response corridors, the model has maximum absolute errors of 3.67 mm and 2.45 deg in head translational and head angular displacements, respectively, in the most optimum solution. The outcomes demonstrate that this head-neck model for a 35th-percentile female can give a high level of accuracy in rear impact simulations.